The Oilfields Workers' Trade Union and the Challenge of Working Class Political Party Formation and Electoral Politics, 1965–1977. Issue 4 (28th November 2016) - Vincent, Godfrey
Abstract : This essay undertakes an examination of the OWTU and the challenge of Working class Political Party formation and Electoral politics, 1962–2012. This area of study has been neglected by Historians and Political Scientists who have tended to focus on the narrow interpretation of the trade union. From 1965 and 1977, the OWTU played significant roles in the creation of the Workers and Farmers Party (WFP) and the United Labor Front (ULF. This essay contends that the union's involvement with these political parties was fraught with difficulties and challenges, and its efforts did not convince the working class that it was in their best interest to support the movement at the polls.